Desain Rekayasa Detail Dinding Penahan Tanah Ruas Jalan Dusun Tapinalu- Ulatu Kecamatan Huamual Kabupaten Seram Bagian Barat - Supusepa, Winaefelia; Siahaya, Vera Theresia Caroline; Latar, Sjafrudin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The road section of Tapinalu-Ulatu Hamlet, located in Luhu Village, Huamual District, Seram Bagian Barat Regency, has a length of 3.1 km and a width of 4.5 m. On the right side of the road, there is a hill and steep slope that caused a landslide at STA 01+150-01+165, with a landslide width of 11 m and a height of 7 m, disrupting road users' activities. This study aims to determine the appropriate type of retaining wall and produce a detailed engineering design.The methods used include calculating active and passive earth pressures using the Rankine method, assessing soil bearing capacity stability with Terzaghi's equation, determining retaining wall dimensions using SNI 2860:2017 standards, and estimating construction costs using the AHSP 2022 Bina Marga method.The results show that the most suitable type of retaining wall for the Tapinalu-Ulatu Hamlet road section is the cantilever retaining wall. The wall meets safety requirements for sliding stability (2.32 ≥ 2 ), overturning stability (2.16 ≥ 2), and bearing capacity (6.88 > 3). The detailed engineering design includes a preliminary design with dimensions: height = 7 m, footing height = 1 m, top width = 0.3 m, base width = 4.8 m, toe width = 1.6 m, and heel width = 2.4 m. The construction cost for the cantilever retaining wall is estimated at IDR 1,913,223.96 m.